What accounts for the increase in female labor force participation in Spain - Victoria Osuna (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
Over the last three decades, Spanish female labor force participation (LFP) has tremendously increased, particularly, that of married women. At the same time, the income tax structure, the fiscal treatment of families, policies to reconcile family and work, and the education distribution of married couples have substantially changed. By contrast, the gender wage gap has remained quite stable. In this paper the author investigates the relevance of these factors in accounting for the growth in Spanish married women labor force participation from 1994 to 2008. For that purpose, she uses Kaygusuz' model of household labor market participation, and data from Eurostat to calibrate the model and evaluate its performance. The model successfully accounts for the rise in aggregate female labor force participation, and matches hours worked by males and females. The model is also able to replicate the pattern of female labor force participation by age and education. From this analysis we can conclude that changes in tax rates and in the education distribution are the main factors behind the increase in female LFP during the late nineties, while changes in child care costs and earning profiles are mainly responsible for the subsequent growth in the 2000s.
Keywords: J11; J12; J13; J22; J31; 330; female labor force participation; gender wage gap; income tax; educational distribution; wage profiles; child care costs